Pengaruh Program Zakat Produktif terhadap Peningkatan Pendapatan Mustahik pada BAZNAS Kota Gorontalo - Lilis B Thaib; Agil Bahsoan, Rierind Koniyo, Frahmawati Bumulo, Fatmawaty Damiti (SEIKO : Journal of Management & Business, 2026)
This study aims to determine the effect of productive zakat programs on increasing mustahik income at BAZNAS Gorontalo City. The research was motivated by the unstable income experienced by several mustahik despite receiving productive zakat assistance. The productive zakat program implemented by BAZNAS Gorontalo City is carried out through business capital assistance, mentoring, and micro-enterprise development as an effort to empower the community’s economy. This study employed a quantitative approach with an associative research design. The population consisted of 106 mustahik recipients of productive zakat, while the sample included 52 respondents selected using the Slovin formula. Data were collected through questionnaires using a Likert scale. Data analysis techniques included descriptive statistics, validity tests, reliability tests, normality tests, and simple linear regression analysis. The results showed that the productive zakat program had a positive and significant effect on increasing mustahik income at BAZNAS Gorontalo City, with a correlation value of 72.9%. The increase in income was indicated by higher business capital, production, turnover, and number of consumers after receiving productive zakat assistance. Keywords: Productive Zakat; Mustahik Income; Economic Empowerment; BAZNAS.